2012
DOI: 10.5402/2012/847870
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage Urethroplasty for Strictures in Maiduguri, North Eastern Nigeria

Abstract: Background. Urethral stricture is a frequent cause of lower urinary tract obstruction worldwide. The aim of this study is to present our experience with one-stage urethroplasty. Methods. All males that underwent one-stage urethroplasty between January 2001 and December 2010 were retrospectively reviewed. Details of their biodata, clinical presentation, diagnostic investigations, operative treatment, postoperative complications, and other outcome of surgery were extracted and analyzed. Results. Ninety-one patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…Chatelain et al [12] reported a scarce urethral stricture of bilharzia origin in a study However, at a mean decline of 12 months 10.3% of the patients did not have good results or 89.7% of success. Ibrahim A. G. et al [13] reported rate inferior to ours at 84.6% of good results in series on the urethroplasties. This difference could be explained by the diversity of follow-up time.…”
Section: Discussioncontrasting
confidence: 62%
“…Chatelain et al [12] reported a scarce urethral stricture of bilharzia origin in a study However, at a mean decline of 12 months 10.3% of the patients did not have good results or 89.7% of success. Ibrahim A. G. et al [13] reported rate inferior to ours at 84.6% of good results in series on the urethroplasties. This difference could be explained by the diversity of follow-up time.…”
Section: Discussioncontrasting
confidence: 62%
“…[ 16 ] in Oshogbo and Ibrahim et al . [ 11 ] in Maiduguri, Nigeria, and in contrast to Tijani et al . [ 17 ] in Lagos, the commercial capital of Nigeria where traumatic cause predominated.…”
Section: Discussionmentioning
confidence: 94%
“…Stricture of the urethra results from narrowing of the urethral lumen due to spongiofibrosis. [ 11 ] The consequence of this is a loss of distensibility and compliance, leading to a reduction in the caliber of the urine stream. Urethral stricture disease is prevalent, and it is a common cause of presentation to the urologist worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Ibrahima Ga et al and Oguike et al, [8] [9]. both studies conducted in Nigeria, reported similar proportions with respectively 38.8% and 35.3% for bulbar location and only 10.4% and 10.3% for the penile location.…”
Section: Discussionmentioning
confidence: 73%